Comparison of Line Dance And Senam Lansia to Improve Cardiorespiratory Endurance In Elderly (Medica Hospitalia : Journal of Clinical Medicine, 2025)
Background: Physical activity in the elderly has a positive impact on promoting healthy aging. Senam lansia is used to be taught to healthy elderly in community however it is boring because of monotonous movement. Line dance is an alternative aerobic exercise that has been taught to elderly. However, there was not any research that compares the effectiveness of both exercises to cardiorespiratory endurance. Aims: This study come to verify that the increase of cardiorespiratory endurance in elderly after line dance was better than senam lansia. Methods: This study was a quasi-experimental pre-test and post-test- controlled group design on 2 groups which was line dance group (n = 20) and senam lansia group (n = 16). The exercise was given based on each group 3 times a week for 6 weeks and VO2max measurement were taken with 6-minute walking test before and after intervention in both groups. Results: The increase of the mean difference/delta VO2max between groups did not differ statistically between groups (line dance: 2,19 ± 3,54 vs senam lansia: 1,79 ± 1,68; p = 0,683). There was a statistically significant difference in the mean pre- and post- intervention VO2max values at line dance group (32,20 ± 3,99; p = 0,013) and senam lansia group (27,03 ± 3,77; p = 0,001). Conclusions: The increase of cardiorespiratory endurance in line dance group and senam lansia group did not differ statistically.